PERLINDUNGAN HUKUM BAGI PENCIPTA LAGU INDIE LABEL DALAM AJANG PENCARIAN BAKAT A MILD WANTED DI BALI PADA TAHUN 2012 - Surya Firdaus, Ade; Supasti Dharmawan, Ni Ketut; Wiratni Darmadi, A. A. Sagung (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014)
This research aims at knowing how the law protection for the A Mild Wanted competition of the talent seeking participant and about the ownership of the copyright of the song which is created in connection with the competition of talent seeking. This research concerns with the research of emphirical law, which have descriptive feature. The location of the research is at Farabi Music School. The kind of the data which is used is the premier data and the seconder data, the technic of collecting data is by interviewing and observing. The data analyses is by qualitative with interactive model.The result of the research shows that the law protection for the copyright of indie song either the copyright creator on the song are protected by law No 19, 2002, mentioned in article 12 for the creation and article 2 for the creator. But in reality, it is still found the divergence from what is concepted in copy right law, the agent who hold the seeking of the talented peopleignorant purposely the right of the indie song creator by using the participant’s song for his promotion without giving the right which must be received by the creator because of the law culture which still has less attention to the protection of the copyright.
Keywords: PERLINDUNGAN HUKUM BAGI PENCIPTA LAGU INDIE LABEL DALAM AJANG PENCARIAN BAKAT A MILD WANTED DI BALI PADA TAHUN 2012